Influence of metal ions on the response of solvatochromic Reichardt indicators: NMR spectroscopic study - Shekhovtsov, S.V.; Lukinova, E.V. (Functional Materials, 2006)
Association of Mg²⁺ and La³⁺ ions with Reiсhardt betaine dyes in deuterated DMSO has been studied using ¹H-NMR method. Basing on chemical shifts of the betaine protons in the presence of metal ions as well as on the chemical shifts of the protonated betaine protons, the Mg²⁺ and La³⁺ ions interaction with the dye molecule has been concluded to be of acid-base nature. The data obtained suggest the inadmissibility of the betaine acid-base sensors in the presence of multicharged metal ions. Асоцiацiю iонiв Mg²⁺ i La³⁺ з бетаїновими барвниками Райхардта у дейтерированому DMSO дослiджена з застосуванням метода ПМР. На пiдставi значень хiмiчних зсувiв протонiв бетаїну у присутностi iонiв металiв, а також хiмiчних зсувiв протонiв протонованого бетаїну зроблено висновок щодо кислотно-основного характеру взаемодiї iонiв Mg²⁺ i La³⁺ з молекулою барвника. Отриманi данi дозволяють зробити висновок про неприпустимiсть застосування кислотно-основних сенсорiв на основi бетаїнiв у присутностi багатозарядних iонiв металiв. Ассоциация ионов Mg²⁺ и La³⁺ с бетаиновым красителем райхардта в дейтерированном DMSO изучена с использованием метода ПМР. На основании значений химических сдвигов протонов бетаина в присутствии ионов металлов, а также химических сдвигов протонов протонированного бетаина сделан вывод о кислотно-основном характере взаимодействия ионов Mg²⁺ и La³⁺ с молекулой красителя. Полученные данные позволяют сделать вывод о недопустимости применения кислотно-основных сенсоров на основе бетаинов в присутствии многозарядных ионов металлов.